Pengaruh Green Marketing Dan Brand Image Terhadap Minat Beli Produk Zorlien Led Yang Dimoderasikan Teknologi Internet (Studi Pada Mahasiswa di Universitas 17 Agustus 1945 Jakarta) - Phamendyta Aldaning Azaria; Nurika Haerul Utami (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
This study aims to examine the effect of green marketing and brand image on buying interest in Zorlien led products with internet technology as a moderating variable. This research was conducted in the areas of Jakarta, Java, Sumatra, Padang, Medan, Lampung. The sampling technique used purposive sampling method. This research data is primary data collected by distributing questionnaires to users of Zorlien led products with a sample of 97 respondents. Hypothesis testing was carried out using the partial least squares (PLS) data analysis method. Based on statistical tests, the results show that green marketing has a positive and significant effect on buying interest, brand image has a positive and significant effect on buying interest, internet technology has a positive and insignificant effect on buying interest. While the moderation of internet technology on green marketing has no significant positive effect on buying interest. Moderation of internet technology on brand image has no significant positive effect on buying interest.